2,3-Diaminopyridinium 3-chlorobenzoate–3-chlorobenzoic acid (1/1) - Madhukar Hemamalini (Acta Crystallographica Section E, 2011)
The asymmetric unit of the title compound, C5H8N3+·C7H4ClO2−·C7H5ClO2, contains an ion pair and a 3-chlorobenzoic acid molecule. In the cation, the pyridine N atom is protonated. In the crystal, the components are connected via N—H...O, O—H...O and C—H...O hydrogen bonds, thereby forming sheets lying parallel to (100).